MEKANISME PEMBATALAN PERATURAN DAERAH OLEH MAHKAMAH AGUNG PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 137/PUU-XIII/2015 DAN NOMOR 56/PUU-XIV/2016 - Islahuddin, Muhammad (Legal Studies Journal, 2024)
The Authority to Revoke Regional Regulations After the Constitutional Court Decision Number 137/PUU-XIII/2015 and Number 56/PUU-XIV/2016 is a type of normative legal research that aims, First, to examine the mechanism of authority to revoke Regional Regulations based on Law Number 23 of 2014 concerning Regional Government after the Constitutional Court Decision Number 137/PUU-XIII/2015 and Number 56/PUU-XIV/2016. This research uses three approaches, namely: Statute approach, historical approach, and comparative approach. Sources of Legal Materials in this research are obtained from primary legal materials and secondary legal materials. The method of analysis in this research uses an analytical descriptive method and then analyzed based on the theory of fiqh dusturiyah, using the deductive method. The results of the study concluded, First, based on Law Number 23 of 2014 concerning Regional Government states that the authority to cancel Regional Regulations is in the hands of the President by delegating his authority to the Minister of Home Affairs and the Governor. The mechanism for canceling Regional Regulations uses two kinds of mechanisms, namely executive preview and executive review. After the issuance of the Constitutional Court Decisions Number 56/PUU-XIV/2016 and Number 137/PUU-XIV/2015, the Government's authority to cancel Regional Regulations has shifted to the Supreme Court through Judicial Review as regulated in Article 24A paragraph (1) of the 1945 Constitution. The Government should supervise regional legal products through preventive supervision (executive preview) by evaluating the Draft Regional Regulation before the Draft Regional Regulation is passed into a Regional Regulation.